2016
DOI: 10.1186/s12909-016-0789-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic real-time feedback is more effective than traditional teaching method in learning ankle joint mobilisation: a randomised controlled trial

Abstract: BackgroundTo analyse the effect of real-time kinematic feedback (KRTF) when learning two ankle joint mobilisation techniques comparing the results with the traditional teaching method.MethodsDouble-blind randomized trial. Settings: Faculty of Health Sciences. Participants: undergraduate students with no experience in manual therapy. Each student practised intensely for 90 min (45 min for each mobilisation) according to the random methodology assigned (G1: traditional method group and G2: KRTF group). G1: an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Traditional teaching methods for learning joint mobilization skills have consisted of an expert instructor demonstrating techniques followed by student practice sessions [21,29,30,58,59]. During these sessions, students typically receive limited objective feedback about the forces applied due to large faculty-student ratios and may continue to practice erroneous motor patterns that adversely affect skill mastery.…”
Section: Joint Mobilization Teaching Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Traditional teaching methods for learning joint mobilization skills have consisted of an expert instructor demonstrating techniques followed by student practice sessions [21,29,30,58,59]. During these sessions, students typically receive limited objective feedback about the forces applied due to large faculty-student ratios and may continue to practice erroneous motor patterns that adversely affect skill mastery.…”
Section: Joint Mobilization Teaching Methodsmentioning
confidence: 99%
“…During these sessions, students typically receive limited objective feedback about the forces applied due to large faculty-student ratios and may continue to practice erroneous motor patterns that adversely affect skill mastery. Previous studies have explored more non-traditional methods of teaching joint mobilization with promising results [29,31,58,59,71]. Gonzalez-Sanchez et al [29] and Triano et al [58,59] utilized quantitative feedback devices with subjects and found that those teaching methods were superior to the traditional approach.…”
Section: Joint Mobilization Teaching Methodsmentioning
confidence: 99%
See 3 more Smart Citations